Evaluation of Medical Officer Certificate Programme Course Competency Based Learning - Saunik, S; Phadke, M; Nair, R; Jakka, P; Menon, P; Patil, A; Kundan, I (Eastern Journal of Medical Sciences, 2017)
Background: Medical Officer Certificate Programme (MOCP) is a 6 months training programme in Pediatrics/Medicine at medical colleges wherein doctors work like postgraduate students, learn various Out Patients and In Patient Department (OPD and IPD) procedures, attain hands on skills, perform day and night duties, attend postgraduate training programmes and specialty clinics. This is a course unique to Maharashtra. It has been designed to overcome shortage of Pediatricians and Physicians in the state. Objective: To evaluate the efficacy of MOCP courses for medical officers by finding out if their clinical skills have improved and if they have achieved expected level of competence. Methods: Public Health Department deputed 28 medical officers of primary health centers. At the end of 6 months training course, they were evaluated during 2012-2013. Results: OPD increased by 24% and IPD by 54%. There was a decrease in the number of cases referred to tertiary centers by 24%, post-MOCP training. Infant immunization increased by 35% after training. Number of children with severe acute malnutrition/moderate acute malnutrition treated increased by 22%, treatment of neonatal emergencies, resuscitation, sepsis, jaundice increased by 36%. Number of adults with diarrhoea and snake bite treated increased by 40% and 63% respectively. Number of ECGs taken and myocardial infarctions managed also has shown rising trend. Conclusion: There was tremendous benefit to the patients after MOCP training. Skill of doctors was found to have enhanced. It is therefore recommended that such novel trainings should be imparted in other states of India too.